KADAR FENOLIK DAN FLAVONOID TOTAL SERTA AKTIVITAS ANTIOKSIDAN DARI EKSTRAK METANOL AKAR, DAUN DAN BUNGA SIMPUR AIR (Dillenia suffroticosa Griff. Ex Hook) - Ginta Rio Maranti; Mustika Furi; Melzi Octaviani; Septi Muharni; Fina Aryani; Husnawati; Wira Noviana Suhery; Musyirna Rahmah Nst; Emma Susanti; Emrizal; Rahayu Utami Utami; Haiyul Fadhli (Jurnal Penelitian Farmasi Indonesia, 2021)
Simpur air is one of plant that has been using as traditional medicine for treating several diseases. Some studies on its chemical constituents and biological activities of this species have been published. However, chemical constituents and antioxidant activity of this plant which is Riau origin has not been reported before. This study aims to determine the total of phenolic and flavonoid content as well as its antioxidant activity of methanol extracts of roots, leaves and flowers of simpur air. Determination of total of phenolic and flavonoid content was performed by spectrophotometric method using Folin Ciocalteu and AlCl3 as reagents, respectively. Whereas, its antioxidant activity was evaluated using DPPH method. The results showed that methanol extracts of its roots afforded the highest total of phenolic and flavonoid content and also its antioxidant activity. The total of phenolic content of methanol extracts of its roots of 428.131 GAE/mg extract; its total of flavonoid content of 766.164 QE/mg extract; as for its antioxidant activity gave IC50 value of 3.852 µg/ml.